Flexural Response of Steel-Concrete Composite Truss Beams - Lisheng Luo; Xiaofeng Zhang (Advances in Civil Engineering)
This paper presents an experimental and analytical study on the flexural response of a steel-concrete composite truss beam. This integrated unit consists of a triangular steel truss, a concrete slab on it, and stud connectors. Three simply supported composite trusses with different configurations of shear connection (η) were evaluated via three-point bending tests. The effects of the shear connectors’ configuration on the flexural response (i.e., load-deflection, load-slippage, and load-strain curves) of the composite trusses were examined. The commercial finite-element (FE) software ANSYS was employed to conduct numerical simulations. An FE model was developed for the composite truss and was validated using experimental results. A parametric study was performed to investigate the effect of the shear connectors’ configuration on the flexural response of the composite trusses. If η < 1, the bending capacity increased with η. In contrast, if η ≥ 1, the effect of η on the bending capacity was negligible. Finally, a design method based on the degree of the shear connection was proposed to predict the ultimate capacity of the composite truss, and the predictions agreed well with the experimental results.